The Development of Mediation for Civil Disputes - QUEK ANDERSON, Dorcas (Institutional Knowledge at Singapore Management University, 2015)
The chapter surveys the major developments in mediation of civil disputes within Singapore and and offer practical suggestions on navigating the civil mediation scene.